(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the proportion of correct knowledge, positive attitudes, and appropriate fall prevention behaviors among nurses in the inpatient departments of Thu Duc City Hospital in 2024, and to identify influencing factors.. Research objects and methods: This study employed a questionnaire to collect data from 269 nurses working in inpatient departments. Quantitative methods were used, including Likert scale measurements and a validated questionnaire with an Alpha coefficient of 0.86. Results: The study revealed that only 19% of nurses possessed adequate knowledge, while 38.3% demonstrated positive attitudes. 86.6% exhibited appropriate fall prevention behaviors. Furthermore, the research indicated that trained nurses displayed 2.1 as positive attitudes and 2.9 times better behaviors compared to untrained nurses. Conclusion: The study highlights significant limitations in the knowledge, attitudes, and behaviors of nurses regarding fall prevention at Thu Duc City Hospital in 2024. Comprehensive, continuous, and structured training programs are necessary to equip nurses with knowledge, raise awareness, and foster positive attitudes toward fall prevention.